Answers

2014-09-07T19:13:43+05:30
As we know cos²A+sin²A=1
⇒cos²A=1-sin²A---------(1)

according to the problem,
sinA+sin²A=1
⇒sinA=1-sin²A--------(2)

therefore: sinA = cos²A

cos²A+cos⁴A = sinA+sin²A = 1
0
2014-09-07T19:16:49+05:30
sinA+ sin^{2} A = 1
or,  sin^{2} A = 1-sinA -----------------(1)
And,
         cos^{2} A+ cos^{4} A = 1- sin^{2} A+ ( cos^{2}A) ^{2}
                                                  =1- sin^{2} A+   [(1-sin^{2}A)] ^{2}
                                                 =1- sin^{2}A + {[1-(1- sinA)]} ^{2}
                                                 =1- sin^{2} A+ sin^{2} A
                                                  = 1
1 2 1